Astrocytic Calcium and cAMP in Neurodegenerative Diseases - Sobolczyk, Marta; Boczek, Tomasz (Frontiers in Cellular Neuroscience, 2022)
It is commonly accepted that the role of astrocytes exceeds far beyond neuronal scaffold and energy supply. Their unique morphological and functional features have recently brough much attention as it became evident that they play a fundamental role in neurotransmission and interact with synapses. Synaptic transmission is highly orchestrated process, which triggers local and transient elevations in intracellular Ca2+, a phenomenon with specific temporal and spatial properties. Presynaptic activation of Ca2+-dependent adenylyl cyclases represent an important mechanism of synaptic transmission modulation. This involves activation of cAMP-PKA pathway to regulate neurotransmitter synthesis, release and storage, and to increase neuroprotection. This aspect is of paramount importance for preservation of neuronal survival and functionality in several pathological states occurring with progressive neuronal loss. Hence, the aim of this review is to discuss mutual relationships between cAMP and Ca2+ signaling and emphasize those alterations at the cAMP/Ca2+ crosstalk that have been identified in neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease.